2021
DOI: 10.1111/papr.13010
|View full text |Cite
|
Sign up to set email alerts
|

Development and Description of a New Multifidus‐Sparing Radiofrequency Neurotomy Technique for Facet Joint Pain

Abstract: Introduction The technique of radiofrequency neurotomy (RFN) of the facet joints has been used for decades to treat persistent low back pain to good effect in carefully selected patients. Traditionally, the target is the medial branches of the dorsal root supplying the facet joint. An alternative denervation target is the facet joint capsule. Capsule‐targeting techniques may spare the multifidus muscle, a possible unintended target of traditional RFN that is thought to be important in recovering from low back … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Multifidus denervation leading to disuse atrophy may cause a vicious cycle of dysfunction among the three spinal stabilizing systems (spinal column, spinal muscles, and neural control unit) causing repetitive tissue injury, suboptimal stabilization of forces, improper tissue overloading, intersegmental spinal instability, impaired sensorimotor control, and chronic nociceptive and neuroplastic changes. Thus, a proposed more conservative multifidus sparing RFA would be preferred targeting the terminal end branches of the medial branch of the dorsal root, directly over the facet joint capsule ( 44 ). Targeting the LMBN has long proven to have therapeutic value.…”
Section: Discussionmentioning
confidence: 99%
“…Multifidus denervation leading to disuse atrophy may cause a vicious cycle of dysfunction among the three spinal stabilizing systems (spinal column, spinal muscles, and neural control unit) causing repetitive tissue injury, suboptimal stabilization of forces, improper tissue overloading, intersegmental spinal instability, impaired sensorimotor control, and chronic nociceptive and neuroplastic changes. Thus, a proposed more conservative multifidus sparing RFA would be preferred targeting the terminal end branches of the medial branch of the dorsal root, directly over the facet joint capsule ( 44 ). Targeting the LMBN has long proven to have therapeutic value.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our anatomical finding, it might be a strategy involving targeted nerve ablation surrounding the facet joint capsule to mitigate potential injury to the medial branch. 32 Previous studies have attributed the low effectiveness of medial branch ablation for LBP to unsuitable patient groups and improper surgical methods. 30 However, our study revealed the presence of an anastomotic branch between two medial branches of different segments.…”
Section: Clinical Relevancementioning
confidence: 99%
“…94 New application forms of radiofrequency are currently under investigation (eg, cooled RF and multi-tined electrodes). 95,96 Other treatment options…”
Section: Alternative Radiofrequency Administration Possibilitiesmentioning
confidence: 99%